(untitled) (GEON Journal (Management, Organizations and Business), 2023)
Problem: the cultivation of the African palm is one of the most dynamic sectors of the national farmer, which has contributed to positioning Colombia as the fourth largest producer of palm oil in the world and the first in the American continent; however, its economic studies they focus on production, cultivated hectares, exports, price, raw materials, employment, etc., leaving out the evaluation of its financial performance. Objective: it seeks to financially diagnose the Colombian company that grows African palm in the period 2017 - 2021. Materials and methods: a static and trend analysis of indicators that measure growth, efficiency in the use of assets, efficacy in costs-expenses monitoring, effectiveness in achieving profits on investment and its Economic Value Added (EVA), which are compared with similar companies nationally and worldwide. Results and discussion: it is found that the farming company varies its sales and assets and net profit; It achieves, on average, accounting returns and its behavior is similar to operating and net profit margins and to asset turnover; although it destroys EVA. Conclusions: when compared with its counterpart with the highest sales in Colombia and with the agricultural company in the global environment, it is found that it is more efficacy in controlling expenditures, but less effective in obtaining benefits on equity; in addition, its international benchmark creates EVA. Contribution/originality: it is an unprecedented comprehensive financial analysis, useful for analysts and businessmen when evaluating their competitiveness. Keywords: financial administration; cost-benefit analysis; profit, crop, vegetable oil.